Openness, ICT and Entrepreneurship in Sub-Saharan Africa - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2017)
This study has examined how information and communication technology (ICT) influences openness to improve the conditions of doing business in sub-Saharan Africa. The data is for the period 2000-2012. ICT is proxied with Internet and mobile phone penetration rates whereas openness is measured in terms of financial and trade globalisation. Ten indicators of doing business are used, namely: (i) cost of business start-up procedures; (ii) procedure to enforce a contract; (iii) start-up procedures to register a business; (iv) time required to build a warehouse; (v) time required to enforce a contract; (vi) time required to register a property; (vii) time required to start a business; (viii) time to export; (ix) time to prepare and pay taxes and (x) time to resolve an insolvency. The empirical evidence is based on Generalised Method of Moments with forward orthogonal deviations. While we find substantial evidence that ICT complements openness to improve conditions for entrepreneurship, the effects are contingent on the dynamics of openness, ICT and entrepreneurship. Theoretical and practical policy implications are discussed. The inquiry is based on two contemporary development concerns: the need for policy to leverage on the ICT penetration potential in the sub-region and the relevance of entrepreneurship in addressing associated issues of population growth such as unemployment.
Keywords: F40; O38; O40; O55; P37; 330; Openness; ICT; Entrepreneurship; Africa